Profitabilitas Sebagai Pemoderasi Pengaruh Pengungkapan Corporate Social Responsibility Pada Nilai Perusahaan - Putri, Kadek Gita Amdika; Gede Wirakusuma, Made (E-Jurnal Akuntansi, 2020)
One of the factors that effect a firm value is Corporate Social Responsibility (CSR). The inconsistency of research results is expected to be able to strengthen CSR profitability in increasing company value. The purpose of this study is to obtain empirical evidence about profitability as a moderating effect of CSR on the value of the mining sector companies listed on the Stock Exchange in the 2016-2018 period. The sampling method used is the nonprobability sampling method with a purposive sampling technique. The number of companies that met the criteria was 11 companies with a total of 43 observations. The data analysis technique used was Moderated Regression Analysis. The results found that CSR not has a effect on firm value. Profitability strengthen the influence of CSR on firm value. The results of this study are expected to be able to provide information for interested parties as a basis for investment decision making. Keywords: Firm Value; Corporate Social Responsibility; Profitability.